The contribution of digital technology to corporate performance - MOKABLI, Asmaa; MILIANI, Fatiha (The International tax journal, 2026)
This article examines how digital technologies contribute to corporate performance by analysing, in turn, the foundations of digitalisation, contemporary organisational transformations, and the impact of digital solutions across operational, commercial, and strategic dimensions. The findings indicate that digital technologies, such as artificial intelligence, big data, cloud computing, the Internet of Things (IoT), and information systems, constitute major levers for efficiency, innovation, and competitiveness. However, the study also highlights several constraints, including adoption costs, skills shortages, cybersecurity risks, ethical issues associated with data, and organisational resistance. The article, therefore, emphasises that successful digital transformation depends on appropriate governance, effective change management, and sustained investment in human capabilities.